DAMPAK SINETRON INDONESIA TERHADAP PERILAKU MASYARAKAT - Azwar, Azwar; Shanti, Hreeloita Dharma; Arumdhani, Kintan (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2019)
This study aims to reveal how people's behavior after watching the soap opera Anak Langit and what are the factors that cause people's behavior to change after watching the soap opera Anak Langit. In addition, this study will also look at how violations that occur in Anak Langit soap operas are based on broadcasting regulations in Indonesia. This research will explore the existing problems using Cultivation Theory where this theory assumes that television exposure impacts on the community. This theory is based on Gerbner's thought which conveys that the continued exposure of the media will give an idea and influence on the perception of the viewer. That is, as long as viewers make contact with television they will learn about the world, change their perception of the world, learn to behave and people's values. This study uses qualitative methods, where researchers conduct literature studies, observations and interviews to approach and explore research problems. Based on this research it can be seen that the soap opera Anak Langit has a negative impact on some of its audience. This is because many violations occur, if guided by broadcasting regulations in Indonesia.